Generation of nitric oxide and induction of major histocompatibility complex class II antigen in macrophages from mice lacking the interferon gamma receptor. - Kamijo, R (1993)
Availability of mice with a targeted disruption of the interferon gamma (IFN-gamma) receptor gene (IFN-gamma R0/0 mice) made it possible to examine parameters of macrophage activation in the absence of a functional IFN-gamma receptor. We asked to what extent other cytokines could replace IFN-gamma in the induction of nitric oxide or major histocompatibility complex class II antigen (Ia) expression in peritoneal macrophages. In thioglycollate-elicited macrophages from wild-type mice, tumor necrosis factor (TNF) alone was virtually ineffective in inducing release of NO2- (the endproduct of nitric oxide generation), but TNF enhanced NO2- release in the presence of IFN-gamma. In macrophages from IFN-gamma R0/0 mice, which were unresponsive to IFN-gamma, TNF completely failed to stimulate NO2- release. The stimulatory actions of IFN-alpha/beta on NO2- release were indistinguishable in wild-type and IFN-gamma R0/0 macrophages: IFN-alpha/beta was ineffective on its own, showed marginal stimulation of NO2- release in combination with TNF, and was moderately effective in the presence of lipopolysaccharide. The level of constitutive Ia antigen expression was not significantly different in peritoneal macrophages from wild-type and IFN-gamma R0/0 mice. An increased Ia expression was induced by IL-4 and granulocyte-macrophage colony-stimulating factor in both wild-type and IFN-gamma R0/0 macrophages, but the magnitude of this induction was less than with optimal concentrations of IFN-gamma in macrophages from wild-type mice. IFN-alpha/beta showed only a minor stimulatory effect on Ia expression in both wild-type and IFN-gamma R0/0 macrophages. Simultaneous treatment of wild-type macrophages with IFN-alpha/beta and IFN-gamma reduced the IFN-gamma-induced Ia expression in wild-type macrophages, but IFN-alpha/beta did not show an inhibitory effect on IL-4- or granulocyte-macrophage-colony-stimulating factor-induced Ia expression in either wild-type or IFN-gamma R0/0 macrophages. The important role of IFN-gamma in the regulation of the induced expression of major histocompatibility complex class II antigen was confirmed by showing that after systemic infection with the BCG strain of Mycobacterium bovis resident peritoneal macrophages from IFN-gamma R0/0 mice had a lower level of Ia expression than macrophages from wild-type mice. The inability of other cytokines to substitute fully for IFN-gamma in macrophage activation helps to explain the earlier observed decreased resistance of IFN-gamma R0/0 mice to some infections.